Does environmental uncertainty of enterprises aggravate the accrual anomaly in the stock market? Evidence from China - Hu, Shuya; Wang, Shengnian (Frontiers in Psychology, 2022)
Enterprises do not exist independently of the external environment, so uncertainty affects their earnings volatility and exacerbates the information asymmetry between internal and external stakeholders. As a major manifestation of capital market mispricing, the accrual anomaly is caused by investors’ functional fixation on total surplus under information asymmetry. Against this backdrop, taking A-share listed companies in China from 2007 to 2019 as our research objects, this study explores the impact of environmental uncertainty on the accrual anomaly based on the information asymmetry and investor irrationality perspective. We find that environmental uncertainty enterprises facing exacerbates the accrual anomaly in the Chinese stock market, and internal control quality, state ownership and the media coverage will affect this impact. Furthermore, this study shows that there are three factors playing the mediating role in the effect, accounting information quality, investment growth and the investor attention. The results show that environmental uncertainty exacerbates the accrual anomaly driven by information manipulation, empire building and investor irrationality. Improving investor irrationality behavior and restraining the self-interest behavior of managers can help alleviate the mispricing of accruals caused by information asymmetry in psychology.